Colorectal intussusception secondary to primary rectal melanoma: A novel case report. (2018) - McQuade, Colin; Waters, Peadar S.; O'Brien, Ciara; Crowther, Stephen; Torreggiani, William; Kavanagh, Dara O.
Highlights: Intussusception in adults is a recognised, but rare, entity. Large bowel intussusception in adults is often due to a malignant neoplasm. Rectal melanoma is a rare condition. This is a novel case of colorectal intussusception secondary to rectal melanoma. Abstract: Introduction: Intussusception in adults is a rare condition, accounting for just 5% of all cases. Approximately 50% of cases of large intestine intussusception occur due to a malignant neoplasm. We present here a novel case report of colo-rectal intussusception arising secondary to a primary rectal melanoma. Presentation of case: We present the case of an 85 year-old patient, who underwent a colonoscopy for investigation of weight loss and altered bowel habit. At colonoscopy, a pigmented polypoid mass was visualised in the upper third of the rectum. The lesion was causing colo-rectal intussusception. Initial biopsies of the specimen stained positive for S-100. The patient had an MRI (magnetic resonance imaging) pelvis, which demonstrated a mass at the rectosigmoid junction, which was diffusely high signal on the fat sat T1 weighted sequence. The patient proceeded to a laparoscopic anterior resection and had an uncomplicated post-operative course. The resected specimen was sent for pathological analysis. The morphological and immunohistochemical profile was consistent with malignant melanoma. There was no evidence of cutaneous melanoma following a full skin examination. Discussion: Rectal melanoma is a rare condition. We present a novel case report of colo-rectal intussusception arising secondary to rectal melanoma. Conclusion: This is a rare entity. This patient's pre-operative MRI and biopsy samples suggested this lesion was a rectal melanoma, which was subsequently confirmed on analysis of the resected specimen. Surgical resection of such neoplasms should be attempted where possible.